DOI: 10.18297/etd/1599
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-student relationships during adolescence : the role of parental involvement, behavioral characteristics, gender, and income.

Abstract: This dissertation provides an examination of contributing factors to high quality teacherstudent relationships during adolescence. High quality teacher-student relationships have been linked to better academic, emotional, and social functioning for students in elementary, middle, and high school. While the importance of teacher-student relationships is well documented, less is know about contributors to the relationship, especially during adolescence. Previous research has identified that in younger population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…In the present study, we also found that the quality of the relationship that adolescent girls in residential care had with their mothers influenced the quality of their relationships with the care workers on their living units. These findings are in line with past studies, which underscore that the quality of adolescents' relationships with their parents correlates with the quality of their relationships with other significant figures (i.e., care workers and teachers; Costa et al, 2020; Wyrick, 2011). In a study of adolescents in residential care, Costa et al (2020) showed that greater insecure‐avoidant attachment in youth was related to more tense relationships with the caregivers on the living unit.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we also found that the quality of the relationship that adolescent girls in residential care had with their mothers influenced the quality of their relationships with the care workers on their living units. These findings are in line with past studies, which underscore that the quality of adolescents' relationships with their parents correlates with the quality of their relationships with other significant figures (i.e., care workers and teachers; Costa et al, 2020; Wyrick, 2011). In a study of adolescents in residential care, Costa et al (2020) showed that greater insecure‐avoidant attachment in youth was related to more tense relationships with the caregivers on the living unit.…”
Section: Discussionsupporting
confidence: 92%
“…The following section will thus review some of the literature on gender differences in levels of loneliness and teacher support. Regarding gender differences in levels of teacher support, some studies have shown that girls tend to report higher emotional support (Låftman and Modin 2012) and a greater degree of closeness with their teachers (Drevets 1996;Wyrick 2011), whereas boys tend to report higher levels of instrumental teacher support (Låftman and Modin 2012). Results from an earlier meta-study by Kelly (1988) moreover suggested that boys tend to have more tangible and instructional contact with teachers than girls.…”
Section: Gender Differences In Perceptions Of the Social Classroom Enmentioning
confidence: 99%
“…Some authors analyse the educational process in schools and universities, and at the same time pay attention to conflict determinants (Character development in schools, 1992; Tavokin, 2012). Others consider individual elements of the educational process, for example, the relationship of students and teachers (Wyrick, 2011;Clark, 2014;Hamre, Pianta, 2006;Ignatova, 2014;Vinokurov, Potapov, 2004). A number of works are devoted specifically to conflicts in educational activities and universities (Vinogradova, Kozina, 2011; Ryapisov, Ryapisova, 2016), as well as the influence of individual factors on the educational process and its elements (Banikina, Stepanov, 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 99%